Flexitarianismo para a sustentabilidade: uma investigação da redução do consumo de carne à luz da teoria da prática - Lima, Cindy Loureen Bernardo (2023)
Meat consumption globally contributes significantly to environmental problems such as reduced biodiversity, freshwater scarcity and climate change. Therefore, dietary changes that replace, reduce or eliminate the consumption of meat and animal products, such as vegan, vegetarian and flexitarian practices, are recognized by the literature as less harmful to the planet. While these diets have recruited more and more followers, studies on them have also multiplied in recent years. While veganism and vegetarianism have received more attention in the literature, flexitarianism has only recently gained attention in the scientific community. As well as most studies on sustainable consumption, these studies have remained at one of the poles of sociological theory, sometimes prioritizing agency, sometimes structure and focusing on developed countries. This work seeks a new look at these practices, or rather, a nexus of practices, by focusing on flexitarianism through the Theory of Practice, assuming the practice per se as a unit of analysis, in the context of a developing country. Thus, the objective of this study was to investigate, in the organization of flexitarian practices, possible contributions to sustainability in the food context of a developing country. Therefore, a qualitative, exploratory and descriptive research was carried out with individuals who are deliberately reducing their meat consumption. The initial contact was made for convenience and, afterwards, the snowball technique was used to capture the subjects. The investigated practices were related to the purchase, preparation and consumption of food, with or without meat. As collection techniques, self-reported diaries were used by the subjects via Whatsapp and interviews based on the diary, following the guidelines of Zimmerman and Wieder (1977). Nine subjects provided information about their eating habits for 7 days. For the analysis of these data, content analysis was used based on the model by Krippendorff (2004) with categorization by Saldaña (2013) and the structure of practice elements proposed by Shove, Pantzar and Watson (2012) (i.e. materials, skills and meanings) for the analysis of practices. The results suggest that the possible contributions of flexitarian practices to sustainability are in the sense of having a lower environmental impact than a totally omnivorous diet, encouraging small producers and local traders and being culturally more acceptable than diets totally restrictive of animal meat. Despite this, there are still elements of these practices that may be unfavorable to sustainability, such as some material barriers (access and price) in the acquisition of meatless foods, meanings related to practicality, convenience and affectivity and the need for nutritional monitoring to ensure adequate nutrition.